1998
DOI: 10.1023/a:1008409601731
|View full text |Cite
|
Sign up to set email alerts
|

Therapy with gemcitabine in pretreated peripheral T-cell lymphoma patients

Abstract: In view of its significant activity and its modest toxicity profile, the role of gemcitabine deserves further evaluation in the management of pretreated patients with peripheral T-cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(58 citation statements)
references
References 9 publications
1
56
1
Order By: Relevance
“…Sallah et al reported an overall response rate of 60% with a 20% CR rate; our previous reports demonstrated a 70% overall response rate with a CR rate of 11%. 13,14 These findings led us to conclude that gemcitabine has the highest activity with acceptable toxicity in previously treated patients with CTCL. For this reason, we decided to use gemcitabine as the frontline treatment of CTCL to evaluate tumor response, as well as the safety and duration of response.…”
Section: Discussionmentioning
confidence: 96%
“…Sallah et al reported an overall response rate of 60% with a 20% CR rate; our previous reports demonstrated a 70% overall response rate with a CR rate of 11%. 13,14 These findings led us to conclude that gemcitabine has the highest activity with acceptable toxicity in previously treated patients with CTCL. For this reason, we decided to use gemcitabine as the frontline treatment of CTCL to evaluate tumor response, as well as the safety and duration of response.…”
Section: Discussionmentioning
confidence: 96%
“…For example, overall response rates of 58-76% (and 41% complete response rate) have been observed in patients with MF/SS treated with low-dose, oral methotrexate [336][337][338][339]. In contrast, for patients with an adequate performance status, single-agent gemcitabine [340][341][342][343][344], pegylated liposomal doxorubicin [345][346][347][348] and pentostatin [349][350][351][352][353][354][355] are frequently utilized (Table VI). Gemcitabine, a pyrimidine nucleoside analog, is associated with overall and complete response rates of 50-70% and 10-20%, respectively, but is associated with neutropenia and nonhematologic toxicities [356].…”
Section: Systemic Chemotherapymentioning
confidence: 99%
“…There is a need to evaluate novel treatment modalities to improve the OS and PFS in the treatment of PTCL. Agents previously investigated include gemcitabine, 12 pralatrexate, 13 allogeneic stem cell transplantation, 14 monoclonal antibodies such as brentuximab, 15 and the histone deacetylase inhibitors (HDACi). 16 …”
Section: Relapsed/refractory Diseasementioning
confidence: 99%